Algorithms for Making Managerial Decisions in the Digital Economy - V. A. Chernov (Управленческие науки)
For solving the existing problems such as loss of sales and customer dissatisfaction, it is necessary to improve promptly the properties of manufactured products in accordance with the dynamically changing market demands. This requires the development of special methods and models for making managerial decisions in conditions of uncertainty and risk. Such decisions could become an algorithm for artificial intelligence of digital technologies, which determines the relevance of the study. The subject of the study is choosing the most significant decisions in conditions of uncertainty and risk. The goal is to find opportunities for making informed decisions for poorly structured, non-formalized processes when developing new product designs with characteristics that meet the rapidly changing needs of the business environment. The solution uses the method of prioritization with expert assessments, groupings, comparisons. The result of the research is the development of a priority setting model with the identification of existing shortcomings and the proposal of changes and additions that eliminate shortcomings in relation to the problem being solved. The author concluded: the developed model, when used in management decisions, allows us to determine the best functions of the product for their inclusion in the design of the innovative model; to make a rating of the significance of functional properties for the consumer and the manufacturer. The development of a methodology with the elimination of the shortcomings of previous studies is a scientific novelty. The obtained methodology contributes to maximizing the demand and competitiveness of the management model, operational innovative changes in the properties of the product corresponding to the rapidly changing demands of the competitive business environment and can be used in the formation of a knowledge base in neural networks of digital technologies. It solves the problem of responding to dynamic changes in consumer preferences, as well as introducing technological innovations in the production of goods, that entail changes in the company’s business processes focused on improving the quality of the final product, which determines the success of strategic business development. The companies’ management may apply the results of the research in the development of corporate governance strategies, researchers, university students, etc.